The Relationship Between Cardiovascular Disease Risk Score and Postoperative Delirium: The PNDABLE Study - Wang, Jiahan; Wang, Li; Tang, Xinhui; Wang, Fei; Liu, Siyv; Wu, Xiaoyue; Dong, Rui; Lin, Xu; Wang, Bin; Bi, Yanlin (Frontiers in Aging Neuroscience, 2022)
Objective We aimed to investigate the relationship between Framingham Heart Study general cardiovascular disease risk score (FHS–CVD risk score) and postoperative delirium (POD) among patients who had unilateral total knee arthroplasty performed under epidural anesthesia. Furthermore, we examined whether such a hypothesized relationship was mediated by the cerebrospinal fluid (CSF) biomarkers. Methods A total of 750 participants were included in the current study. And the data were drawn from the database obtained from the Perioperative Neurocognitive Disorder And Biomarker Lifestyle (PNDABLE) study. The preoperative cognitive function of participants was measured by using Mini-Mental State Examination (MMSE). The incidence of POD was assessed using the Confusion Assessment Method (CAM). The POD severity was measured using the Memorial Delirium Assessment Scale (MDAS). The POD CSF biomarkers included in the current study were: Aβ42, T-tau, P-tau, Aβ42/T-tau, and Aβ42/P-tau. The level of the CSF biomarkers was measured using the enzyme-linked immune-sorbent assay (ELISA) in the PNDABLE study. Linear regression analysis was performed to examine the relationship between the FHS–CVD risk score and the POD CSF biomarkers. Logistic regression was used to analyze the relationship between FHS–CVD risk score, POD CSF biomarkers, and POD incidence. The proposed mediating effect of CSF biomarkers was evaluated using Mediation Analysis with 10,000 bootstrapped iterations. The receiver operating characteristic (ROC) curve is chosen as the evaluation metric for assessing the efficacy of the FHS–CVD risk score in predicting POD. Results In the PNDABLE study, the overall incidence of POD was 22.9% with 37.2% in the higher vascular risk group and 7.9% in the lower vascular risk group. Multiple linear regression models showed that a higher preoperative FHS–CVD risk score was positively correlated with CSF T-tau (β = 0.218, P = 0.015) and P-tau level (β = 0.309, P < 0.001) in the higher vascular risk group. After adjusting for age (40–90 years), gender, education, MMSE, smoking history, drinking history, hypertension, diabetes, and the presence of CHD (cardiovascular heart disease), the results of the logistic regression analysis demonstrated the effect of Aβ42 (OR = 0.994, 95% CI 0.992–0.996, P < 0.001), Aβ42/T-tau (OR = 0.353, 95% CI 0.254–0.491, P < 0.001), and Aβ42/P-tau (OR = 0.744, 95% CI 0.684–0.809, P < 0.001) in protecting patients against POD. However, the FHS–CVD risk score (OR = 1.142, 95% CI 1.017–1.282, P = 0.025) and the remaining two biomarkers: T-tau (OR = 1.005, 95% CI 1.004–1.007, P < 0.001) and P-tau (OR = 1.045, 95%CI 1.029–1.062, P < 0.001) were identified as the risk factors. Mediation analyses revealed that the association between FHS–CVD risk score and POD was partially mediated by T-tau (proportion: 31.6%) and P-tau (proportion: 23.6%). The predictive power of the FHS–CVD risk score was validated by the ROC curve with an AUC of 0.7364. Conclusion Higher vascular risk score is one of the preoperative risk factors for POD, which is partly mediated by CSF biomarker tau protein. Clinical Trial Registration [www.clinicaltrials.gov], identifier [ChiCTR2000033439].